2016
DOI: 10.1021/acsphotonics.6b00198
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Percolation in Nearly Closed Gold Films

Abstract: Metal–dielectric composites exhibit remarkable properties at the percolation threshold. A small variation of the filling factor can lead to a huge variation in the dc conductivity from an insulator-like to a metal-like behavior while the real part of the permittivity diverges. This behavior can, in principle, be described by percolation theories at low frequencies and by effective medium approximations at higher frequencies. These theories assume a random distribution of the metallic inclusions inside the insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In the first case, an interband plasmonic origin was claimed for the resonances. In the second case, it was proposed that the oxynitride consists of a mixture of two phases that mimics at the macroscopic scale the visible optical response of an interband plasmonic material, in an analogous way to an earlier report from De Zuani et al [108] that showed huge effective 1 values (up to 1000!) in nearly closed Au films.…”
Section: Discussionmentioning
confidence: 61%
“…In the first case, an interband plasmonic origin was claimed for the resonances. In the second case, it was proposed that the oxynitride consists of a mixture of two phases that mimics at the macroscopic scale the visible optical response of an interband plasmonic material, in an analogous way to an earlier report from De Zuani et al [108] that showed huge effective 1 values (up to 1000!) in nearly closed Au films.…”
Section: Discussionmentioning
confidence: 61%
“…As the average film thickness increases during the metal deposition, individual and well-separated metal islands extend their sizes, eventually forming near the percolation threshold a semicontinuous film that gradually evolves into a homogeneous smooth film exhibiting (close to) bulk properties . The percolation threshold can experimentally be observed by monitoring FE effects with optical methods , and uniquely determined in the low-frequency regime through electric conductivity measurements. , It should also be noted that the average film thickness corresponding to the percolation threshold depends strongly on the deposition conditions, substrate material, and metal involved. , …”
mentioning
confidence: 99%
“…64 In general, the divergency of the dielectric permittivity e 1 (x) is a hallmark of percolative phase transitions in microemulsions, [65][66][67][68][69] composites [70][71][72] or and percolating metal films. [73][74][75][76][77] Since audio-and radio-frequency experiments are more suitable for exploring the dielectric behavior at the insulatormetal transition, we have conducted dielectric experiments down to 7.5 kHz. Fig.…”
Section: Dielectric Propertiesmentioning
confidence: 99%